13N-Ammonia Combined With 18F-FDG Could Discriminate Between Necrotic High-Grade Gliomas and Brain Abscess. (March 2015) - Shi, Xinchong; Yi, Chang; Wang, Xiaoyan; Zhang, Bing; Chen, Zhifeng; Tang, Ganghua; Zhang, Xiangsong
Abstract : Purpose: Accurate prediction of brain abscess is beneficial for timely management. In this study, we investigated the utility of 13 N-ammonia and its combination with 18 F-FDG in differentiating brain abscess from necrotic high-grade gliomas. Patients and Methods: Thirteen patients with ring-like enhancement high-grade gliomas and 11 patients with brain abscess were recruited in our study. All of them underwent both 18 F-FDG and 13 N-ammonia PET imaging. Lesion uptake was evaluated by lesion to normal gray matter ratio (L/N). Histopathology diagnosis was obtained for all the patients after PET imaging. Results: The L/N values of 18 F-FDG were not significantly different between brain abscess and necrotic high-grade gliomas ( P = 0.35). The uptake of 13 N-ammonia in gliomas was higher than that in abscess lesions (L/N: 1.38 ± 0.31 vs 0.84 ± 0.18, P < 0.001). The receiver operating characteristic curve analysis determined the optimal L/N cutoff value ( 13 N-ammonia) of 1.0 with the area under the curve of 0.94 and the overall accuracy of 87.5%. Discriminant analysis demonstrated that the combination of 18 F-FDG and 13 N-ammonia could distinguish the 2 clinical entities with higher accuracy of 95%, and only 1 necrotic glioma lesion was misclassified into the abscess group. Conclusions: 13 N-ammonia is effective in distinguishing brain abscess from necrotic high-grade gliomas, and its combination with 18 F-FDG could further elevate the diagnostic accuracy.